Real options implicit in a food distribution company - Gutiérrez Urzúa, Mauricio (2014)
The present study focuses on the valuation of a project through real options. It suggests that the flexibility that this type o projects have provides a value added to it, considering that the fact of being able to decide the most appropriate time to expand given the different potential scenarios in the long term. In particular, it is desired to valuate the option of deferring the expansion strategy through the construction of branches in various cities of the country It was possible to infer that the real option of postponing an expansion project generates an additional value, mainly due to the benefit of opening an branch before schedule, considering the risk effect and variability.